2003
DOI: 10.1074/jbc.m206006200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the Proglucagon Gene by Lithium and β-Catenin in Intestinal Endocrine L Cells

Abstract: The proglucagon gene encodes several peptide hormones that regulate blood glucose homeostasis, growth of the small intestine, and satiety. Among them, glucagon-like peptide 1 (GLP-1) lowers blood glucose levels in patients with diabetes and inhibits eating and drinking in fasted rats. Although proglucagon transcription and GLP-1 synthesis were shown to be activated by forskolin and other protein kinase A (PKA) activators, deleting or mutating the cAMP-response element (CRE) only moderately attenuates the progl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 72 publications
6
84
0
Order By: Relevance
“…In addition, Wnt signalling molecules and Frizzled receptors are expressed in the endocrine pancreas of both mice and humans [12,16,33] and regulate insulin secretion [17] and beta cell proliferation [19]. In contrast, the canonical Wnt signalling pathway cannot be activated in glucagon-producing alpha cells [34,35]. We investigated canonical (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Wnt signalling molecules and Frizzled receptors are expressed in the endocrine pancreas of both mice and humans [12,16,33] and regulate insulin secretion [17] and beta cell proliferation [19]. In contrast, the canonical Wnt signalling pathway cannot be activated in glucagon-producing alpha cells [34,35]. We investigated canonical (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, regulation of proglucagon gene expression by the Wnt signaling pathway has recently been demonstrated in enteroendocrine L cells. However, regulation of proglucagon gene expression by lithium via this pathway has not been shown in pancreatic ␣ cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Since previous reports have demonstrated that GLP-1 receptor agonists inhibit β-cell apoptosis under conditions of glucolipotoxicity 46,47 and that PPARβ/δ activation also prevents palmitate-induced β-cell apoptosis 28 , we speculated that the protective effect of PPARβ/δ on β- Further, it has been established that lithium, a GSK-3β inhibitor, and insulin increase proglucagon expression through stimulation of the β-catenin-TCF/Lef signaling pathway only in enteroendocrine GLP-1-producting L cells, but not in pancreatic glucagon-producing α-cells 26,27 . This is due to the fact that the transcription factor TCF-4 is expressed in small intestine epithelium 39 , but not in islet α-cells 27 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insulin and GSK-3β inhibitors, such as lithium, stimulate G2 response element activity specifically in enteroendocrine L cells through the β-catenin/TCF-4 signaling pathway resulting in increased GLP-1 production 26,27 .…”
Section: Introductionmentioning
confidence: 99%